Control interno de las cuentas por cobrar del GAD Municipal de Puebloviejo para el periodo 2021-2022. - Uriarte Loor, Dayana Hael (2024)
The present investigation on the topic: Internal control of accounts receivable of the Municipal Gad of Puebloviejo for the period 2021-2022, the financial documents were reviewed where the problem could be verified in the deficiencies of the internal control of accounts receivable in an entity. public, which causes problems in the portfolio, late payments, etc. It is justified by the need for improvements to ensure resources. The conceptual framework addresses concepts of internal control, components, accounts receivable, etc. The methodology applied is qualitative and quantitative, through questionnaires and financial analysis. The results obtained show weaknesses in records, debtor monitoring and collection work. In the conclusions section it is verified that internal control in this collection area is inadequate. It is recommended to designate a person in charge, implement an integrated computer system, carry out periodic reconciliations and training. The purpose of this study is to understand the problem and identify specific improvements to strengthen the control of accounts receivable in areas of efficient public management. In addition, analyze each of the accounts receivable from the financial statements for the 2021-2022 period of the organization mentioned above, for which tools were established that will help us understand the situation of the institution and will contribute to my study of case.